Special Police Team Towards the Bright Point Brigadier Joshua's Murder Case - Junaedi; Try Gustaf Said (East Asian Journal of Multidisciplinary Research, 2023)
The obstacles faced by the police in uncovering this case are 1). Police officers have cleared the crime scene; 2). Brigadier J's HP Lost; 3). Witness Shut Up; 4). Other Obstacles regarding CCTV at the Office House Damaged; 5). Putri Candrawati is a key witness who is still alive. The bright spots for the cases that led to the death of Brigadier J include 1. The presence of Tita President Joko Widodo; 2. There is suspicion of premeditated murder; 3. It has been obtained and turned on CCTV cameras around the crime scene that are lost or dead; 4. Brigadier J's cellphone and CCTV have been examined in a forensic laboratory based on the Scientific Crime Investigation processed by a forensic laboratory; 5. There is a re-autopsy. To open the veil of Brigadier J's case based on President Joko Widodo's order, the National Police Chief finally named a suspect in the shooting case that killed Brigadier Yoshua Hutabarat, based on 1). Initial evidence is sufficient; 2). Other possible suspects; 3). The threat of punishment (Bharada E; 4). Bharata E was arrested; 5). Not self-defense; 6). Murder suspect; 7). Initial chronology.